Tautomerism of 5-Methyl Imidazolidine Thio Derivatives in the Gas Phase: A Density Functional Study - Zaki S. Safi; Fakhr M. Abu-Awwad (E-Journal of Chemistry)
Relative tautomerisation energies, enthalpies, entropies, Gibbs free energies, and dipole moments for 5-methyl-2,4-dioxo-imidazolidine and its thio analogous have been studied in the gas phase using hybrid density functional at the B3LYP level of theory using 6-31(d) and 6-311+(2df,2p) basis sets with full geometry optimization. A comparative investigation of their energies revealed that the keto form of the compound is the predominant tautomer with a very high tautomeric energy barrier. The findings conclude that the intramolecular prototropic tautomerisation process is thermodynamically unfavored.